What about Children and Gender?. Issue 1 (31st December 2022) - Silber, Laurel
ABSTRACT: When contextualizing childhood gender expression within an attachment system, a more elaborate picture emerges of what it might be about. This essay serves as a summary of a more contemporary psychoanalytic theoretical consideration of a controversial subject and its' application to clinical work with children and their families. Gender is embodied and children use their bodies to regulate affects and communicate what is on their mind. This summary emphasizes the importance of an adults' reflective stance, i.e.one that is playful, for the purposes of helping a child create a coherent narrative of their experience.